2013
DOI: 10.1111/iej.12118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium hypochlorite associated with EDTA and etidronate on apical root transportation

Abstract: The use of NaOCl associated with etidronate increased apical transportation in the canals of extracted teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
2
15
2
Order By: Relevance
“…Agarwal et al (17) showed that at 3-mm above the apex ProTaper and WaveOne groups showed transportation towards the lateral side of the canal curvature while the OneShape group remained centred, which collaborate with the results of this study. This result differs from previous studies that indicate that the apical segment usually has more canal transportation toward the outside of the curve (25) .…”
Section: Discussioncontrasting
confidence: 99%
“…Agarwal et al (17) showed that at 3-mm above the apex ProTaper and WaveOne groups showed transportation towards the lateral side of the canal curvature while the OneShape group remained centred, which collaborate with the results of this study. This result differs from previous studies that indicate that the apical segment usually has more canal transportation toward the outside of the curve (25) .…”
Section: Discussioncontrasting
confidence: 99%
“…This result differs from previous studies that indicate that the apical segment usually has more canal transportation toward the outside of the curve. 19,22,25 As in the present study, an average deviation from the direction of the different thirds was used, and hence our results probably reflect the higher incidence of deviation inside of the curve that occurs in the cervical and middle segments, as previously reported by Stavileci et al 9 An important difference between the NiTi systems used in the present study is related to the number of the files used. ProTaper and Twisted File systems use a small number of files in an attempt to simplify the root canal instrumentation, whereas Hero and Liberator systems allow the use of a larger number of instruments.…”
Section: Discussionsupporting
confidence: 67%
“…5,8,13,16,17,18,19 Satisfactory results have been obtained with the root serial section technique, 16 radiographic platform, 18 and root resin canal simulation. 17 However, more accurate information can be achieved with micro-computed tomography (micro-CT) 6,13 and computed tomography (CT), 1,7,8,20 which allows for the quantitative and qualitative evaluation of root canals in 3 dimensions.…”
Section: Discussionmentioning
confidence: 95%
“…A reduction in dentin microhardness caused by irrigating solutions used in endodontic treatments not only can facilitate the preparation of narrow or calcified canals, but also it may increase the chances of canal deviation to occur [2, 23]. …”
Section: Discussionmentioning
confidence: 99%